Estimating a consumer demand system of energy, mobility and leisure. A microdata approach for Germany. - Beznoska, Martin (My University, 2014)
This paper investigates empirically the consumer demand of environmentally relevant goods for Germany, as well as their relationship to the demand for leisure. Higher prices for energy goods like gas, electricity or fuel oil due to higher indirecttaxation amongst others may have serious welfare and distributional effects for households. Also, there is very little evidence of the labor market implications of environmental taxation, as there is e.g. no quantification of labor supply effects, respectively leisure demand effects for Germany. Using a demand system to estimate the price, cross-price and income effects of the goods mobility, electricity, heating and leisure from microdata, there will also be accounted for the extensive demand for leisure, which is the not negligible labor market participation. Additionally, the extensive and intensive leisure demand is combined to total leisure demand elasticities, which can then be used for welfare and behavior analyses.
Keywords: Umweltschutz; Steuer; Energie; Verbraucherverhalten; Umweltbelastung; Freizeit; Verkehr; Mobilität; Freizeitverkehr; Heizung; Energieverbrauch; Einkommensverteilung; Politikinstrument; Ökosteuer; Energienachfrage